2011
DOI: 10.1007/s10584-011-0198-2
|View full text |Cite
|
Sign up to set email alerts
|

Study on forest fire danger over Northern China during the recent 50 years

Abstract: Daily meteorological data at 263 stations in northern China from 1956 to 2005 were used to calculate various forest fire danger weather (FFDW) indices, such as Nesterov Index (NI), Modified Nesterov Index (MNI), Keetch-Byram Drought Index (KBDI), and Forest Fire Danger Index (FFDI), at different time scales. The relationship between each index and forest fire was analyzed. MNI and FFDI were then selected to study the impact on forest fire danger due to climatic change in northern China in the recent 50 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Both climate change and human factors are likely to continue to transform grasslands in northern China. Climate projections for north-eastern China include higher temperatures along with lower precipitation and relative humidity (Niu and Zhai 2012). Projected changes in the wind regime are as yet unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both climate change and human factors are likely to continue to transform grasslands in northern China. Climate projections for north-eastern China include higher temperatures along with lower precipitation and relative humidity (Niu and Zhai 2012). Projected changes in the wind regime are as yet unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Climate change and human factors are likely to continue to transform grasslands in northern China. Climate projections for north-eastern China predict higher temperatures along with lower precipitation and relative humidity Niu and Zhai (2012). Liu et al (2012) also indicated that the expected change in population density is correlated with temperature as well as the change in precipitation.…”
Section: Discussionmentioning
confidence: 95%
“…Generally, the forest area or wildland has the high possibility to have forest fires and to have a significant damage to the environment (Ramachandran et al, 2008). According to the statistics of China, from 1952 to 2012, there were 798,500 forest fires and 38,060,000 hectares of forest was destroyed, which caused about $22m loss a year (Niu and Zhai, 2012). There exist complex factors that cause forest fires, among which local weather and human behaviors are the factors that mostly relate to forest fires.…”
Section: Forest Fire Predictionmentioning
confidence: 99%
“…Wildfires occur much more frequently in the south than in the north, while burned area has an opposite spatial pattern (Chang et al, 2015;Chen et al, 2017;Li et al, 2015;Lv et al, 2006;Tian et al, 2013). Many regions have two fire seasons in spring and fall and large interannual variability (Niu & Zhai, 2012;Yi et al, 2017) due to local, regional, and global atmospheric processes (Yao et al, 2017;Zhang et al, 2016). Efforts have been made to use atmospheric factors to predict seasonal fire activity in China (Chang et al, 2013;Li et al, 2014;Sun & Zhang, 2018).…”
Section: 1029/2019gl081932mentioning
confidence: 99%